The effect of air conditioning positions, air conditioning fluid speed, and temperature on thermal comfort in the truck cabin - Turgut, Emre; Yardimci, Ugurcan (Korean Soc Mechanical Engineers, 2022)
The effects of air conditioning parameters in the truck cabin on thermal comfort were numerically investigated using ANSYS. Air conditioner positions, fluid velocities coming out of air conditioner vents, and outlet temperatures of the fluid were determined. In the analysis, three different air conditioning positions, three different temperatures, and six different speeds were used. Predicted mean vote (PMV) and predicted percentage of dissatisfied (PPD) values were calculated according to the results obtained. The best average PMV was found in position 2 with -0.055781108, whereas the worst average PMV was found in position 3 with -1.112957448. The best average PPD value was found in position 2 with 5.12, and the worst average PPD value was found in position 3 with 31.63. In addition to PMV graphics, temperature and velocity distributions in the truck cabin are given with contour graphics. All the data obtained were evaluated together to determine the best combination.
Keywords: Air-conditioning; Computational fluid dynamics (CFD); Predicted mean vote (PMV); Thermal comfort; Truck cabin